Effects of Apatinib on the Pharmacokinetics of Nifedipine and Warfarin in Patients with Advanced Solid Tumors - Zhu YT; Teng Z; Zhang YF; Li W; Guo LX; Liu YP; Qu XJ; Wang QR; Mao SY; Chen XY; Zhong DF (Dove Medical Press, 2020)
Yun-Ting Zhu,1,* Zan Teng,2,3,* Yi-Fan Zhang,1 Wei Li,1 Li-Xia Guo,1 Yun-Peng Liu,2,3 Xiu-Juan Qu,2,3 Quan-Ren Wang,4 Si-Yuan Mao,4 Xiao-Yan Chen,1 Da-Fang Zhong1 1State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai, People’s Republic of China; 2Department of Medical Oncology, The First Hospital of China Medical University, Shenyang, People’s Republic of China; 3Key Laboratory of Anticancer Drugs and Biotherapy of Liaoning Province, The First Hospital of China Medical University, Shenyang, People’s Republic of China; 4Department of Clinical Research and Development, Jiangsu Hengrui Medicine Co., Ltd., Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi-Fan Zhang; Da-Fang ZhongState Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, 501 Haike Road, Shanghai 201203, People’s Republic of ChinaTel/ Fax +86 21 50800738Email yfzhang@simm.ac.cn; dfzhong@simm.ac.cnBackground and Purpose: Apatinib is a small-molecule tyrosine kinase inhibitor for the treatment of recurrent or progressive advanced-stage gastric adenocarcinoma or gastroesophageal junction cancer. The in vitro inhibition studies suggested that apatinib exerted potent inhibition on CYP3A4 and CYP2C9. To evaluate the potential of apatinib as a perpetrator in CYP450-based drug–drug interactions in vivo, nifedipine and warfarin were, respectively, selected in the present study as the probe substrates of CYP3A4 and CYP2C9 for clinical drug–drug interaction studies. Since hypertension and thrombus are common adverse effects of vascular targeting anticancer agents, nifedipine and warfarin are usually coadministered with apatinib in clinical practice.Methods: A single-center, open-label, single-arm, and self-controlled trial was conducted in patients with advanced solid tumors. The patients received a single dose of 30 mg nifedipine on Day 1/14 and a single dose of 3 mg warfarin on Day 3/16. On Day 9– 21, the subjects received a daily dose of 750 mg apatinib, respectively. The pharmacokinetics of nifedipine and warfarin in the absence or presence of apatinib was, respectively, investigated.Results: Compared with the single oral administration, coadministration with apatinib contributed to the significant increases of AUC0– 48h and Cmax of nifedipine by 83% (90% confidence interval [CI] 1.46– 2.31) and 64% (90% CI 1.34– 2.01), respectively. Similarly, coadministration with apatinib contributed to the significant increases of AUC0-t and Cmax of S-warfarin by 92% (90% CI 1.68– 2.18) and 24% (90% CI 1.10– 1.39), respectively.Conclusion: Concomitant apatinib administration resulted in significant increases in systemic exposure to nifedipine and S-warfarin. Owing to the risk of pharmacokinetic drug–drug interactions based on CYP3A4/CYP2C9 inhibition by apatinib, caution is advised in the concurrent use of apatinib with either CYP2C9 or CYP3A4 substrates.Keywords: apatinib, drug-drug interaction, CYP3A4, CYP2C9, nifedipine, warfarin